Topological and spatial heterogeneity of gut microbiota co-abundance networks in pigs revealed by using large-scale samples - Wu, Lin; Liu, Yuxin; Chen, Congying; Gao, Jun (Frontiers in Microbiology, 2025)
Fecal samples have often been used as a proxy for studying the gut microbiota. However, the fecal microbiota does not fully reflect the gut microbiota composition. To elucidate the biogeographical characteristics and interaction networks of porcine gut microbiota, we systematically determined the compositions and co-abundance networks of gut microbiota from small to large intestine using 2,955 microbial samples from ileum, cecum, and feces of F6 (715) and F7 (687) pigs which were slaughtered at the age of 240 days from an experimentally designed heterogeneous pig population by crossing eight divergent breeds using 16S rRNA gene sequencing. The gut microbial composition showed significant spatial heterogeneity. The diversity of the gut microbiota progressively increased along the intestinal tract. Significantly spatial heterogeneity was also observed in the co-abundance networks. The numbers of OTUs showing co-abundance correlations with other OTUs were increased from ileum to cecum and feces. We found that the stronger the co-abundance correlation, the higher the gut location specificity of the co-abundance relationships. Only 644 (0.2%) co-abundance relationships among OTUs existed in all three gut locations. Prevotella had the highest number of stable co-abundance relationships, followed by Bacteroidales, Bacteroides, S24-7, and Lachnospiraceae. Topological analysis found that the co-abundance network of OTUs in the ileum showed random network characteristics, while the co-abundance networks of OTUs in the cecum and feces showed the scale-free network characteristics in both pig populations. Compared with the co-abundance networks in the cecum and feces, the networks in the ileum had fewer nodes, but more edges, indicating that the ileum microbiota was a microbial ecosystem with a smaller number of microbial species, but closer interactions. However, the pairwise co-abundance correlations between OTUs were more independent in the cecum. The co-abundance network in the ileum had the lowest stability, but the highest vulnerability, while the co-abundance network in the cecum exhibited the highest stability, but low vulnerability. Finally, we characterized the gut location-specific microbial co-abundance relationships. Characterizing the different phylogenetic structures of gut microbiota in different intestinal biogeographic niches would help to explore the spatial heterogeneity of microbial physiological functions and to develop the strategy regulating gut microbiota targeting to specific gut locations.